Allogeneic peripheral blood stem cell transplantation using reduced‐intensity conditioning in an outpatient setting in ABO‐incompatible patients: are survival and graft‐versus‐host disease different?. Issue 5 (28th October 2013) - Gutiérrez‐Aguirre, Cesar Homero; Gómez‐De‐León, Andrés; Alatorre‐Ricardo, Julio; Cantú‐Rodríguez, Olga Graciela; González‐Llano, Oscar; Jaime‐Pérez, José Carlos; Mancías‐Guerra, Consuelo; Flores‐Jiménez, Juan Antonio; Gómez‐Almaguer, David
<x xml:space="preserve">Abstract</x> Background Graft‐versus‐host disease (GVHD) is a major cause of morbimortality after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Minor ABO incompatibility has been associated with an increased risk of GVHD. We analyzed the impact of ABO matching on patient outcome after peripheral blood, reduced‐intensity allo‐HSCT in an outpatient setting, and its relationship with GVHD. Study Design and Methods Data of 121 patients were included. All patients received allo‐HSCT from HLA‐identical siblings as outpatients using a reduced‐intensity conditioning regimen. Influence of ABO matching as a risk factor for the development of GVHD and survival was analyzed using logistic regression and Cox proportional hazards regression, respectively. Results Median age was 36 years (range, 1‐71 years); 88 patients were ABO identical: 13 presented major mismatch and 20 minor mismatch, with an ABO incompatibility rate of 27.3%. The median follow‐up period was 54 months (range, 0.3‐120 months). Minor ABO incompatibility patients presented the highest rate of acute GVHD (aGVHD; 25%), in comparison with ABO‐identical (20.5%) and major ABO incompatibility patients (15.4%; p = 0.79). The highest incidence of chronic GVHD (cGVHD) occurred in the context of minor ABO incompatibility (35%), in contrast to ABO‐identical (30.8%) and major ABO incompatibility (15.4%). Survival was higher for patients in the minor ABO mismatch group; however, there was no significant correlation between ABO matching status and survival (p = 0.45). Conclusion Using this type of peripheral blood stem cell transplantation, minor ABO‐mismatched allo‐HSCT was associated with a higher incidence of aGVHD and cGVHD and with increased survival, albeit with no significance.